Anaemia in Bovines: Haematobiochemical Alterations with Diagnostic and Clinical Significance - Shanavas, Arjun; Mosing, Peyi; Mahendran, K; Akshata, Bhand (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Anaemia in bovines is a multifactorial disorder influenced by nutritional deficiencies, parasitism, infectious agents, and metabolic  imbalances. The present study was conducted to evaluate haematological and biochemical alterations associated with anaemia in bovines.  Blood samples were collected from clinically suspected animals and compared with healthy controls. Haematological evaluation revealed  significant reductions in haemoglobin concentration, packed cell volume, and erythrocytic indices in anaemic animals, confirming  impaired erythropoiesis. Biochemical analysis demonstrated alterations in protein, iron, and related metabolic parameters, reflecting  the underlying nutritional and pathological disturbances. These findings emphasize the complex etiology of anaemia in bovines and  underline the importance of integrated diagnostic approaches for timely detection and effective management. The outcomes of this  study contribute to a better understanding of bovine anaemia and provide a baseline for field diagnosis and preventive strategies.
Keywords: Bovine anaemia; Nutritional deficiency; Parasitism; Iron metabolism; Veterinary diagnostics